Outreach Schools: An Educational Innovation - Housego, Billie E. J. (Alberta Journal of Educational Research, 1999)
To benefit those students who cannot or will not pursue their educations in traditional high schools, that is, to prevent their leaving before graduation or to facilitate their return if they do leave prematurely, educators continue to address the problem of providing alternate educational programs. This study of Outreach Schools, a current system of alternative education, was conducted through staff and student interviews, student questionnaires, school visits, and an exploration of related literature. The school philosophy is outlined, the teachers and students are described, the operation of the schools is explained, and a case is made for this type of educational alternative.